The Profitability of Momentum Strategies: Empirical Evidence from Damascus Securities Exchange (DSE) - Mahmoud, Oubay; Wardeh, Almougheer I (International Journal of Business, Economics and Management, 2018)
The purpose of this study is to examine the profitability of Momentum based- trading strategies and investigate the causes of such profitability in Damascus Securities Exchange (DSE) market. The study analyzed 16 Momentum strategies based on full rebalancing and equally weighted techniques using monthly data from January 2010 to December 2016. The findings of the study showed low but significant Momentum effect, where the returns of Momentum portfolios were statistically positive only in 1 out of 16 strategies. Our findings suggest that Momentum strategy is applicable for winner portfolios whereas contrarian strategy is more appropriate for loser portfolios. We also adopted Market Model in order to investigate the possible risk-based explanations of Momentum profits, but we found that market risk is unable to explain the Momentum profitability in DSE market.